Youth of Bangladesh: : Readying them Demographic Dividend (Bangladesh Journal of Public Administration, 2022)
At present one-third of Bangladesh's population is under the age of thirty. Additionally, Bangladesh's working-age population (15–59%) is currently bigger than the non-working-age population (>15 and 60+), which has the potential to propel economic growth with a focus on our youth. Although there is a lot of interest in Bangladeshi adolescents, there is relatively little thorough information available about their situation. This research was conducted to offer insightful information about our youngsters. The youth's self-identities and life goals were first observed, together with their level of education and skill readiness, and then their engagement in earning activities. Then, a survey was conducted to determine how free they felt to choose. Their political stance was then examined. From the analysis, it can be said that Bangladeshi youth are still mostly untapped and are not at all prepared to take advantage of the prospects presented by the twenty-first century. This is especially true for young women and those from underprivileged socioeconomic backgrounds.Keywords: ; ; Goals of life; Preparedness for future; 4IR.